Уровень корпоративной культуры как основное конкурентное преимущество предприятия - Ганус, А.И.; Иваницкий, В.Д. (Культура народов Причерноморья, 2013)
Уровень корпоративной культуры рассматривается как неотрицательный показатель
нравственного климата организации. Он служит важнейшим нематериальным фактором
конкурентоспособности предприятия. Приведен усредненный профиль корпоративной культуры
предприятия, который является взвешенной системой четырех типов культуры, предложенных
Камероном. Для обеспечения конкурентного преимущества эту систему следует проектировать при
помощи экспертных оценок желательных изменений в культуре предприятия. Рівень корпоративної культури розглядається як додатній показник морального клімату
організації. Він являється найважливішим нематеріальним фактором конкурентоспроможності
підприємства. Наведено середній профіль корпоративної культури, який є збалансованою системою
чотирьох типів культури, запропонованих Камероном. Для забезпечення конкурентної переваги цю
систему слід проектувати за допомогою експертного оцінювання бажаних змін у корпоративній
культурі. The corporate culture’s level is considered as a non-negative measure of the moral climate in the
organization. It is the most important intangible factor in the company's competitiveness. It is proposed in the
paper to don’t share the corporate culture of commercial organizations into positive and negative, as
competitiveness cannot be negative. Culture, as a set of common values and as skills of their creation, either
absent (vandalism and other forms of anti-social behavior) or positive, but at the same time are characterized by
the level, which needs to rise, increasing the humanistic orientation of the organization. The average profile of
the company’s corporate culture, which is a weighted system of four types of culture (proposed by Cameron),
was built. To gain a competitive advantage this system of four culture types can be designed using expert
estimates desired change in the culture of a particular company. Four types of interpersonal staff were proposes
in the paper, which forming the steps of increase the humanistic fullness of corporate culture and, therefore, the
growth of its competitiveness.